Ammonia recovery from high concentration wastewater of soda ash industry with membrane distillation process. Issue 15 (27th March 2016) - Wu, Chunrui; Yan, Hanhan; Li, Zhengang; Lu, Xiaolong
Abstract: Vacuum membrane distillation was applied in the treatment of high ammonia content wastewater for the recovery of ammonia. Hydrophobic poly(vinylidene fluoride) hollow fiber membranes were used as the separation media. The initial ammonia concentration and pH value of the feed solution were destined owing to the composition of the wastewater. The effects of feed temperature, velocity, and operation time on the ammonia removal efficiency, separation factor, and water content in produced ammonia vapor were studied. The results showed that feed temperature was the most important factor affecting ammonia removal efficiency, which was improved from 78 to 99% as the temperature enhanced from 30 to 60°C. The feed velocity and operation time also affected the ammonia removal efficiency and separation factor obviously. A pilot-scale experiment was carried out using a membrane module of 20 m 2 membrane area. Preliminary results showed that proper ammonia removal efficiency and product property were obtained.